Increased brain and atrial natriuretic peptides in patients with chronic right ventricular pressure overload: correlation between plasma neurohormones and right ventricular dysfunction. Issue 1 (1st July 2001) - Tulevski, I I; Groenink, M; van der Wall, E E; van Veldhuisen, D J; Boomsma, F; Stoker, J; Hirsch, A; Lemkes, J S; Mulder, B J M
Abstract : OBJECTIVE: To evaluate the role of plasma neurohormones in the diagnosis of asymptomatic or minimally symptomatic right ventricular dysfunction. SETTING: Tertiary cardiovascular referral centre. METHODS: Plasma brain natriuretic peptide (BNP) and atrial natriuretic peptide (ANP) concentrations were measured in 21 asymptomatic or minimally symptomatic patients with chronic right ventricular pressure overload caused by congenital heart disease, and in seven healthy volunteers. Right ventricular ejection fraction was determined using magnetic resonance imaging. RESULTS: Right ventricular ejection fraction in the volunteers was higher than in the patients (69.0 (8.2)% v 58.0(12.0)%, respectively; p < 0.006). Left ventricular ejection fraction was 72.3(7.8)% in volunteers and 68.1(11.0)% in patients (NS). There was a significant difference between patients and volunteers in the plasma concentrations of BNP (5.3 (3.5) v 2.3 (1.7) pmol/l, respectively; p < 0.009) and ANP (7.3 (4.5) v 3.6 (1.4) pmol/l; p < 0.05). In both patients and volunteers, mean plasma ANP was higher than mean plasma BNP. Right ventricular ejection fraction was inversely correlated with BNP and ANP (respectively, r = 0.65; p < 0.0002 and r = 0.61; p < 0.002). There was no correlation between left ventricular ejection fraction and BNP ( r = 0.2; NS) or ANP ( r = 0.52; NS). Similarly, no correlation was shown between the level of right ventricular systolic pressure and either plasma BNP ( r = 0.20) or plasma ANP ( r = 0.07). CONCLUSIONS: There was a significant inverse correlation between right ventricular ejection fraction and the plasma neurohormones BNP and ANP in asymptomatic or minimally symptomatic patients with right ventricular pressure overload and congenital heart disease. Monitoring changes in BNP and ANP may provide quantitative follow up of right ventricular dysfunction in these patients.